Development of a Numerical Simulation Model for Continuous Floating Cryopreservation of Red Blood Cell Concentrate - Kamphaus, Lisa; Khayyat, Diaa; Kahlfeld, Robin; Hagedorn, Janina; Kabelac, Stephan; Glasmacher, Birgit (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):286